Follicular residua of spontaneously regressed congenital melanocytic nevus - Milano, A.; Colonna, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
A 4-month-old little girl entered a prospective study on congenital melanocytic nevus because she presented since birth a 2 x 0.6 cm, intensely pigmented nevus on the front surface of the right leg (Fig. 1). The dermoscopic examination showed a bluish uniform pigmentation with superimposed black net and peripheral globules (Fig. 5). At a control examination 1 year later the pigmentation significantly decreased and tended to be distributed around the hair follicles (Fig. 2, 6). This tendency got more evident at the control after 2 years (Fig. 3, 7). After 7 years from the first visit in the site of the nevus only hypertrofic hair follicles with scarce perifollicular pigment were glimpsed (Fig. 4, 8). At this age the final diagnosis was follicular residua of spontaneously regressed congenital melanocytic nevus.